Two Novel Semisynthetic Lipoglycopeptides Active against Staphylococcus aureus Biofilms and Cells in Late Stationary Growth Phase - Vladimir Vimberg; Leona Zieglerova; Aninda Mazumdar; Zsolt Szűcs; Aniko Borbás; Pál Herczegh; Gabriela Balikova Novotna (MDPI AG, 2021)
The increase in antibiotic resistance among Gram-positive bacteria underscores the urgent need to develop new antibiotics. New antibiotics should target actively growing susceptible bacteria that are resistant to clinically accepted antibiotics including bacteria that are not growing or are protected in a biofilm environment. In this paper, we compare the in vitro activities of two new semisynthetic glycopeptide antibiotics, MA79 and ERJ390, with two clinically used glycopeptide antibiotics-vancomycin and teicoplanin. The new antibiotics effectively killed not only exponentially growing cells of Staphylococcus aureus, but also cells in the stationary growth phase and biofilm.